Effect of intratrigonal botulinum toxin in patients with Bladder Pain Syndrome/Interstitial Cystitis: A 10 year, single center, retrospective study - António Ferrão Mendes (2022)
Background: Bladder Pain Syndrome/Interstitial Cystitis (BPS/IC) is associated with a high percentage of failure in long term response to pharmacological therapy. Surgical or intravesical therapy can be used in refractory patients. The intratrigonal injection of botulinum toxin A (OnaBotA) previously revealed good short and mid-term effectiveness and safety in past studies. We aimed to evaluate the long-term efficacy and adverse events of this procedure and determine the predictors of long-term responders. Methods: A retrospective cohort study included 50 patients with BPS/IC treated with botulinum toxin in a tertiary university hospital, between the years 2009 and 2022. Of those, we focused more on a subset of long-term responders: underwent 5 or more injections. The clinical and surgical records of the individuals, including the results using a 10-point visual analogue scale (VAS), were utilized for the analysis of data related to the interventions. Results: In our cohort we had 20 long-term responders with up to 14 interventions per patients. We observed that the time of the effect of the injections seems to be constant throughout treatment (p=0,54). The most frequent side effects per procedure were straining (17,68%) and cystitis (16,43%). Neither age (60,2 vs. 58,3; p=0,7), basal VAS (5,5 vs 6; p=0,9); or mean time between the injections (520 vs 586 days; p=0,5) were predictors of long-term responders. Conclusion: Intratrigonal injection of botulinum toxin in patients with BPS/IC is a safe and effective long-term treatment option. Age, basal VAS and time between the injections does not seem to predict that a patient will not be a long-term responder to OnaBotA.